Estratégias metacognitivas para leitura e compreensão de textos : avaliação de uma proposta no contexto do ensino de física - Ribeiro, Cássia de Andrade Gomes (2021)
This Research begins with the necessity of contributing with the qualification of Physics’ teaching and learning process, through the use of metacognitive strategies associated with the interpretation of texts. The study advocates the importance of using texts in Physics teaching, as well as the potential of explicit use of metacognitive strategies during didactic activities. The investigation questions the way these strategies can be associated with the reading of scientific texts in the teaching of Physics, pointing out that those present in the literature do not sufficiently contemplate the set of elements considered to be part of the understanding of metacognition in the sense of Rosa (2011) and derivative from the studies of Flavell (1976; 1979) and Brown (1978; 1987). With this statement, followed by the need of developing a proposal that contemplates the metacognitive elements announced by the mentioned authors, the question that guided the study was formulated: how can the metacognitive strategies, as a didactic possibility, contribute to qualify the reading and comprehension of a text? With this, the general goal of the study was outlined to analyze the relevance of a model of metacognitive strategies developed for the reading and comprehension of texts in Physics classes. To answer this question and achieve the proposed goal, the study developed a proposal for the use of metacognitive strategies based on the use of quoting, circumscribing it in a sequence of constructivist teaching. The teaching sequence was structured in five meetings and developed in the ninth grade group from a private Elementary School, in the town of Nova Prata, Rio Grande do Sul. The research took a qualitative approach to evaluate, through the notes of metacognitive strategies usage when students proceeded to read texts guided by metacognitive questions. In addition to this assessment, the study used questions of metacognitive consciousness applied at the beginning and at the end of the teaching sequence, as well as semi-tructured interviews with the participants from the study. The results of the questioning of metacognitive consciousness, interviews and logbook records allow us to infer that the proposed strategy model becomes relevant, as the use of the metacognitive reading guide favors the evocation of metacognitive thinking, presenting itself as an alternative for improving text comprehension. Finally, the study points out the need to share metacognitive reading strategies, so that they are available to teachers so that they can implement them in their teaching practices. Thus, the study originated a support material that compiles metacognitive reading strategies present in the literature and the strategy model proposed in the present study, it consists of the educational product of this dissertation, available in: <https://educapes.capes.gov.br/handle/capes/598616>.